Structure-property relationship in charge transporting behaviour of room temperature liquid crystalline perylenebisimides - Prajitha, K. P.; Chithiravel, Sundaresan; Krishnamoorthy, K.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A homologous series of pentadecyl phenol functionalized perylenebisimide (PBI) terminated with trialkoxy gallate esters was synthesized, where the terminal alkyl chain length was varied from n = 4 to 12 (PBI-En). The thermotropic liquid crystalline (LC) characteristics of the molecules were analyzed using differential scanning calorimetry (DSC), polarized light microscopy (PLM) combined with variable temperature wide angle X-ray diffraction (WXRD) techniques. A clear odd-even oscillation was observed in the melting as well as isotropization enthalpies as a function of alkyl spacer length in the terminal gallate unit, with the even spacers exhibiting higher values. The higher members of the series with n > 8 exhibited thermotropic liquid crystalline textures in the PLM, which remained stable until room temperature. The nature of the LC phase was identified to be columnar rectangular and columnar hexagonal based on detailed analysis of the WXRD pattern recorded in the LC phase. The WXRD pattern of the room temperature LC frozen samples indicated a nearly constant intra columnar stack distance of similar to 3.7 angstrom for all the members. The space-charge-limited current (SCLC) values of the LC frozen sample films were analyzed for dependence of the bulk mobility estimate on the nature of the LC phase. The columnar hexagonal phase exhibited a mobility value one order (10(-3) cm(2) V-1 s(-1)) higher than that of crystalline (10(-4) cm(2) V-1 s(-1)) and two orders higher than that of columnar rectangular phase (10(-5) cm(2) V-1 s(-1)), indicating a strong dependence of packing on bulk mobility.